Caracterización de residuos sólidos alimentarios como materia prima para alimentación animal - Itza Ortiz, Mateo Fabian (2024)
The objective of the study was to use solid food waste, generated by the maquiladora industry, as an input for the production of flour for pig feed purposes and to determine the bacterial load before and after its transformation into a safe food input. The fresh solid food waste was subjected to a dehydration process to transform it into flour and was subsequently pelleted. Microbial analyses of fresh, flour, and pelleted solid food waste were carried out according to the Mexican standard NOM-109-SSA1-1994 and NOM-113-SSA1-1994. The presence of coliforms, Staphylococcus aureus, Salmonella spp, and Listeria monocytogenes were quantified. The presence of Staphylococcus aureus in fresh solid food waste was 33.30 %, coliforms 14.28 %, Salmonella spp 4.76 %, and Listeria monocytogenes 0 %, compared to solid food waste in flour and pellets (0.0 %). In conclusion, solid food waste in flour can be used as an input in the preparation of a balanced diet for pigs feeding with an inclusion until of 45 %. The microbiological analysis of the fresh solid food waste indicated a percentage of pathogenic microorganisms much higher than those established by the standard. However, the dehydration process is sufficient to eliminate them.